2021
DOI: 10.1111/jbi.14113
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics under the Massenerhebung effect: The influence of topography on the demography of Acer morrisonense

Abstract: Aim The Massenerhebung effect (Mass elevation effect) refers to heat‐ or wind‐driven altitudinal distribution patterns of temperature‐dependent parameters among massifs with narrower range and lower elevation around peripheral and isolated mountains compared to core and continuous ones. Although common in ecology, this effect is rarely discussed in population genetics. Here, we use genetic markers to reveal population genetic patterns and also test the mountain‐ and sky‐barrier hypotheses relevant to the Masse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…According to PNC, the distribution range of the most suitable habitat varies temporally with climate change. ENM in this study indicated that A. caudatifolium upward shifted to mountain ranges after the LGM ( Figure 2 ), in contrast to the downward expansion of A. morrisonense from high mountains (Figure 5 of [ 7 ]). Among all maples in Taiwan, these two species have the closest phylogenetic relationship but are not sister species [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…According to PNC, the distribution range of the most suitable habitat varies temporally with climate change. ENM in this study indicated that A. caudatifolium upward shifted to mountain ranges after the LGM ( Figure 2 ), in contrast to the downward expansion of A. morrisonense from high mountains (Figure 5 of [ 7 ]). Among all maples in Taiwan, these two species have the closest phylogenetic relationship but are not sister species [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 74%
“…Like A. morrisonense , the chlorotypes of A. caudatifolium are differentiated from north to south (Figure 2b of [ 7 ]). However, the north-south differentiation of A. caudatifolium resulted from the collection of different ancient populations ( Figure 2 ), whereas divergent alpine refugia were responsible for the differentiation of A. morrisonense (Figure 5 of [ 7 ]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations